Dopant radial inhomogeneity in Mg-doped GaN nanowires. (25th April 2018) - Siladie, Alexandra-Madalina; Amichi, Lynda; Mollard, Nicolas; Mouton, Isabelle; Bonef, Bastien; Bougerol, Catherine; Grenier, Adeline; Robin, Eric; Jouneau, Pierre-Henri; Garro, Nuria; Cros, Ana; Daudin, Bruno
Abstract: Using atom probe tomography, it is demonstrated that Mg doping of GaN nanowires grown by Molecular Beam Epitaxy results in a marked radial inhomogeneity, namely a higher Mg content in the periphery of the nanowires. This spatial inhomogeneity is attributed to a preferential incorporation of Mg through the m-plane sidewalls of nanowires and is related to the formation of a Mg-rich surface which is stabilized by hydrogen. This is further supported by Raman spectroscopy experiments which give evidence of Mg-H complexes in the doped nanowires. A Mg doping mechanism such as this, specific to nanowires, may lead to higher levels of Mg doping than in layers, boosting the potential interest of nanowires for light emitting diode applications.